AffectAura: An Intelligent System for Emotional Memory - McDuff, Daniel; Karlson, Amy; Kapoor, Ashish; Roseway, Asta; Czerwinski, Mary (Proceedings of the ACM Conference on Human Factors in Computing Systems (CHI '12), 2012)
We present AffectAura, an emotional prosthetic that allows users to reflect on their emotional states over long periods of time. We designed a multimodal sensor set-up for continuous logging of audio, visual, physiological and contextual data, a classification scheme for predicting user affective state and an interface for user reflection. The system continuously predicts a user's valence, arousal and engagement, and correlates this with information on events, communications and data interactions. We evaluate the interface through a user study consisting of six users and over 240 hours of data, and demonstrate the utility of such a reflection tool. We show that users could reason forward and backward in time about their emotional experiences using the interface, and found this useful.